Effects of sodium bicarbonate supplementation on performance and gastrointestinal symptoms during a high-intensity training session in elite rugby players: a double-blind randomized controlled trial - Couce, B.; Baos, S.; Moreno-Villanueva, A.; Recarey-Rodríguez, A. E.; Mielgo-Ayuso, J.; Martínez-Ferrán, M. (Sports, 2026)
Background: Sodium bicarbonate (SB) supplementation can enhance performance in short, high-intensity movements. However, its effectiveness in team sports such as rugby remains insufficiently explored.